Characterization of kaolinite/emulsion-polymerization styrene butadiene rubber (ESBR) nanocomposite prepared by latex blending method: Dynamic mechanic properties and mechanism. (September 2020) - Zhang, Ao; Zhang, Yinmin; Zhang, Yongfeng
Abstract: The latex blending method was chosen to prepare Kaolinite/emulsion-polymerization styrene butadiene rubber (ESBR) nanocomposite to improve the interaction between filler particles and rubber matrix chains. The influences of kaolinite particles size, filler contents, and flocculants types on dynamic mechanical properties and the relative reinforcement mechanism of the prepared composite were systematic investigated and proposed. The transmission electron microscopy (TEM) and scanning electron microscopy (SEM) showed that the kaolinite particles were finely dispersed into the rubber matrix and arranged in parallel orientation. The prepared nanocomposites by latex blending exhibited improved crosslinking characteristic and dynamic mechanical parameters. The KAl (SO4 )2 flocculant presented obvious modification in dynamic properties and crosslinking characteristic. Both the decrease in kaolinite particle size and the increase in kaolinite content can greatly improve the storage modulus and reinforcing effect of kaolinite/ESBR nanocomposites. The dynamic reinforcement mechanism of kaolinite can be explained by filler network including a certain thickness of rubber shell on the surface of kaolinite lamellar structure and the aggregations network between kaolinite particles The optimum way to balance the dynamic properties of rubber nanocomposites at different temperatures is to reduce the surface difference between kaolinite and rubber matrix and the degree of filler-filler networking on the basis of kaolinite with nanoscale (nanometer effect). Highlights: A novel prepared method-latex blending was utilized to improve the dispersion of kaolinite in ESBR matrix and obtain a semi-exfoliation type clay/polymer composite. The dynamic properties of prepared rubber composites were improved, and thus the dynamic reinforcement mechanism of kaolinite was proposed. The micromorphology of kaolinite layer-like particles presented loose and blurry in rubber matrix, and which resulted in the reduction of kaolinite crystal order degree.